Design, simulation and characterization of 50nm p-well MOSFET using Sentaurus TCAD Software - Marlia, Morsin; Mohd Khairul Amriey; Abdul Majeed, Zulkipli; Rahmat, Sanudin (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.